Senior citizens satisfaction with the services of the Department of Health : its relationship to their involvement in community activities - Ruiz, Ariston P. (Laoag City : [s.n.], 2019)
This study determined the senior citizens' (SCs) satisfaction level with the health services of the Department of Health and its relationship to their involvement in community services in the different barangays of Laoag City for fiscal year (FY) 2017. It described the profile of the SCs, their satisfaction level with the government's health-related services, their involvement in community services, and the relationship between these variables.
Bibliography: pages 81-83.
CHED-La Union
Keywords: Elderly